Marriage in the Jahiliyah Era and Islamic Response to Pre-Islamic Wedding Traditions - Afifa Tuljanah; Adelia Islamipasyah; Didik Himmawan; Ellysia (Diplomasi : Jurnal Demokrasi, Pemerintahan dan Pemberdayaan Masyarakat, 2025)
This study intends to examine pre-Islamic culture, Arab society before the arrival of Islam, was not a society that was sterile from the influence of religion, customs, morals and rules of life that already existed among them. Once Islam came with all the norms in it, Islam became a filter for the culture, customs and beliefs that already existed among pre-Islamic Arab society. The research approach in this study is Library Research, which is a study carried out using literature (library) in the form of books, notes or research reports from previous studies. The results of this study, In this study it can be concluded that during the jahiliyah era there were many forms of marriage, four types of marriage are discussed in this study. Three forms of marriage, namely Al-Istibda Marriage, Al-Rath Marriage, Al-Rayah Marriage, are forbidden in Islamic law. Al-Wiladah Marriage is the one that is prescribed in Islam. A man or a young man comes to the parents of the girl/woman to propose to her then he marries her accompanied by a dowry or dowry and ijab qabul. Marriage is justified because it aims to produce offspring. Al-Wiladah Wedding is a wedding performed by the Prophet Muhammad SAW.